Exposure to maternal nicotine in utero and/or via lactation alters craniofacial development in mice. - Amr Mohi; Emily L Durham; Rajiv Kishinchand; James J Cray (PLoS ONE)
The Center for Disease Control's National Birth Defects Prevention Study data suggests that maternal nicotine use may increase the incidence of craniofacial birth defects and growth anomalies like craniosynostosis, cleft palate, and/or lip in offspring. Craniofacial growth proceeds by expansion at fibrous sutures and synchondroses. In the cranial base, synchondroses, which are cartilaginous joints, play a major role in craniofacial development including neurocranial expansion and facial outgrowth. Our previous data showed alterations in craniofacial structures with intrauterine exposure to nicotine. As the use of nicotine is increasing among youths, especially through use of electronic nicotine delivery systems, there is a great need to investigate the critical periods of nicotine exposure during pregnancy and postnatal development. Alterations in craniofacial growth that occur in response to maternal nicotine use must be understood in order to prevent debilitating conditions. For this investigation, we utilized cephalometric and histomorphometric analyses to investigate how nicotine exposure alters craniofacial development in offspring modeling maternal nicotine exposure either during pregnancy and lactation or post-partum lactation only compared with unexposed controls. Our results in mice showed significant changes in craniofacial dimensions and some specificity for effects in the synchondroses across the three experimental groups including significant changes in the cellular and the extracellular collagen matrix components of these growth centers. The most dramatic effects segregated to the lactation only exposed group, which is a major target from a prevention point of view as there is a common misconception among the public that nicotine cessation during pregnancy is sufficient for prevention of ill effects in the offspring.